TAKSONOMI IKAN DI SUNGAI GONDANG DESA TANDING MARGA KECAMATAN SUNGAI ROTAN KABUPATEN MUARA ENIM - Dian mutiara (Universitas PGRI Palembang, 2013)
Research of taxonomy of fishs at Gondang river Tanding Marga village, Muara Enim regency Sumatera Selatan province on Oktober-November 2012. This research utilited the direct observation method by collecting fish samples which were caught by fisherman along Gondang river. The result of the research geted 4 order, 15 family, 23 genera and 27 species.Key words : Taxoonomy, fish, Gondang river